Design and control of microstructure and texture by thermomechanical processing of a multi-phase TiAl alloy. (5th October 2017) - Erdely, Petra; Staron, Peter; Maawad, Emad; Schell, Norbert; Klose, Joachim; Clemens, Helmut; Mayer, Svea
Abstract: Sheets made of intermetallic γ-TiAl based alloys possess promising engineering properties for lightweight high-temperature applications. Due to the complexity of their manufacturing, however, they are still not fully commercialised. Recently, a manufacturing route has been introduced for β-stabilised γ-TiAl based alloys that is effectively abridged compared to the conventional ingot metallurgy route. The present work explores the impact of each proposed processing stage on a β-solidifying, multi-phase Ti-43.5Al-4Nb-1Mo-0.1B (in at.-%) alloy. Texture measurements using synchrotron radiation were conducted and combined with microstructural analyses. The experiments allowed to fundamentally correlate the processing, which included heat treatment steps for balanced mechanical properties, with the evolution of both microstructure and texture. Thereby, the influences of deformation, recovery and recrystallisation, and phase transformations could be identified. The results reveal several options to optimise the material properties within the cost-effective manufacturing route. One option discussed in depth is the layout of the temperature profile in connection with the exploitation of the prevailing phase transformations. The presented findings are expected to improve the future design of γ-TiAl based sheet manufacturing routes. Graphical abstract: Highlights: The evolution of texture and microstructure was studied during the processing of Ti-43.5Al-4Nb-1Mo-0.1B (in at.-%) sheets. The texture of the majority γ phase is characterised by recrystallisation and phase transformation components. During sheet manufacturing, the texture of all phases remains weak, minimising the potential for mechanical anisotropies.